Research on Digital Transformation in Higher Education: Present Concerns and Future Endeavours - Rahmadi, Imam Fitri (TechTrends, 2024)
The massive emergence of digital technologies requires not only enterprises but also educational institutions to transform their strategies and values for maintaining competitiveness. While research on digital transformation in higher education is becoming more available in the literature, structured examinations regarding their concerns are scarce. Through a systematic literature review with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) model, this standalone overview examines principal concerns of research on digital transformation in post-secondary education, nominates better practices and lines upcoming investigations. Results indicate that considerable attention has been paid to the strategies and barriers to digitally transforming universities whilst leadership was marginally explored. The practice of this transformation may be centralised in pedagogical innovations supported by organisational measures and led by transformational leadership. Digital transformation leadership, evidence-based maturity assessment and integrated technological, pedagogical and organisational measures are imperative areas for future research. The present review contributes to the early development of studies on digital transformation in higher education.